Effects of rice husk biochar application on the properties of alkaline soil and lentil growth - S. Abrishamkesh; M. Gorji; H. Asadi; G.H. Bagheri-Marandi; A.A. Pourbabaee (Plant, Soil and Environment, 2015)
This study evaluated the effects of biochar application on some properties of an alkaline soil and on lentil (Lens culinaris Medik) growth. Lentils were grown in the soil amended with the rates of 0.4, 0.8, 1.6, 2.4, and 3.3 weight percent of two biochars (B1 and B2), produced from rice husk under different pyrolysis conditions. Lentils were harvested after 70 days. Soil samples were also analysed for changes in physico-chemical properties. The results indicated that biochar application significantly increased soil organic carbon, cation exchange capacity, available potassium and below ground biomass of lentil, while it decreased soil bulk density. The results suggested that biochar application to alkaline soils has benefits to both soil quality and plant growth.